2012
DOI: 10.1007/s10637-012-9803-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening of drugs to counteract human papillomavirus 16 E6 repression of E-cadherin expression

Abstract: Persistent infections with certain high-risk human papillomavirus (HPV) types such as 16 and 18 can result in the development of cervical cancer. Neither of the two prophylactic vaccines against HPV16 and 18 that are in current use have any therapeutic efficacy for prevalent HPV infections. Ablative therapy is widely used for the treatment of HPV cervical dysplasia however disease recurrence is a widely recognized problem. Thus there is a continuing need for therapeutic approaches for the treatment of HPV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…1B). We have previously shown that HPV16 E6 expression (transiently) in an immortalized keratinocyte cell line, HaCaT, reduces surface E-cadherin expression by around half [14] and that surface E-cadherin expression is similarly reduced in HCT116 cells stably expressing E6 [18]. HCT116 cells are widely used to study E-cadherin regulation [19][21] being intact in the major E-cadherin repressor pathways such as E-box-mediated repression [20] and having low levels of promoter methylation [22].…”
Section: Resultsmentioning
confidence: 99%
“…1B). We have previously shown that HPV16 E6 expression (transiently) in an immortalized keratinocyte cell line, HaCaT, reduces surface E-cadherin expression by around half [14] and that surface E-cadherin expression is similarly reduced in HCT116 cells stably expressing E6 [18]. HCT116 cells are widely used to study E-cadherin regulation [19][21] being intact in the major E-cadherin repressor pathways such as E-box-mediated repression [20] and having low levels of promoter methylation [22].…”
Section: Resultsmentioning
confidence: 99%
“…However, human KCs transfected with HPV8 E7 protein exhibited decreased CCL20 expression by preventing binding of C/EBP to the CCL20 promoter [67] , suggesting a possible mechanism for HPV oncoprotein interference with KC-derived CCL20, which attracts LCs. Similarly, lower E-cadherin expression on HPV-infected KCs is correlated with cervical lesion severity [59] , [68] , [69] and reduced numbers of LCs in HPV-infected epidermis [60] , [70] . In vitro , inhibition of HPV16 E6 and E7 oncoproteins restored E-cadherin expression and LC adhesion to KCs [69] , [70] .…”
Section: Impact Of Hpv Infection On Antigen Presentation To the Adaptmentioning
confidence: 95%
“…Similarly, lower E-cadherin expression on HPV-infected KCs is correlated with cervical lesion severity [59] , [68] , [69] and reduced numbers of LCs in HPV-infected epidermis [60] , [70] . In vitro , inhibition of HPV16 E6 and E7 oncoproteins restored E-cadherin expression and LC adhesion to KCs [69] , [70] . Together, these data imply that recruitment and localization of DCs to HPV-infected epithelia may hamper accessibility of HPV proteins to APCs and this may in part contribute to failure to generate effective anti-HPV CTL responses.…”
Section: Impact Of Hpv Infection On Antigen Presentation To the Adaptmentioning
confidence: 95%
“…High-risk E6s are capable of activating NF-κB (D’Costa et al, 2012; Havard et al, 2005; James et al, 2006b; Nees et al, 2001; Yuan et al, 2005). The mechanism is not entirely clear although there is evidence that it may interact with the PDZ binding motif (James et al, 2006b).…”
Section: Biological Functions Of E6mentioning
confidence: 99%